1993
DOI: 10.1161/01.atv.13.10.1449
|View full text |Cite
|
Sign up to set email alerts
|

Age influences the replicative activity and the differentiation features of cultured rat aortic smooth muscle cell populations and clones.

Abstract: The replicative activity and the differentiation features of aortic smooth muscle cells (SMCs) cultured as whole populations or clones from newborn (4-day-old), young adult (6-week-old), and old (18-month-old) rats were studied by means of cell counting, [3 H]thymidine incorporation, and measurement of the expression of cytoskeletal proteins and mRNAs. In whole populations at the fifth passage, replicative activity increased and differentiation features (ie, expression of o-smooth muscle actin, desmin, and smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 37 publications
7
62
1
Order By: Relevance
“…18,24 In the present study, SMC marker expression was very similar in the populations of neointimal SMCs cultured after either stent or PTCA. Both populations maintained the expression of all markers, including smoothelin, at passage 5, indicating a SMC rather than a fibroblastic origin.…”
Section: Smc Marker Expression In Cultured Cellssupporting
confidence: 59%
“…18,24 In the present study, SMC marker expression was very similar in the populations of neointimal SMCs cultured after either stent or PTCA. Both populations maintained the expression of all markers, including smoothelin, at passage 5, indicating a SMC rather than a fibroblastic origin.…”
Section: Smc Marker Expression In Cultured Cellssupporting
confidence: 59%
“…47 ' 48 IT-15 cells, however, showed a significantly lower contractile activity than IT-60 and control SMCs. It has recently been shown that a proportion of clones deriving from medial SMCs from old rats show dedifferentiated features, contrary to clones derived from young adult or newborn animals 13 ; this correlates with dedifferentiated features of cultured populations of SMCs from old rats. 13 Further experiments that involve cloning SMCs from intimal thickening or the underlying media at different intervals after endothelial denudation could answer the question as to whether these clones behave similarly to those produced from medial cells of young and old animals.…”
Section: Cell-populated Collagen Lattice Contractionmentioning
confidence: 95%
“…It is noteworthy, however, that SMC clones with different properties can be isolated from the rat aorta of normal animals at different ages. 13 Our experiments were performed to verify whether, after endothelial denudation, SMC activation (1) affects, in addition to intimal thickening, cells of the underlying media and (2) persists in intimal cells 60 days after injury, when endothelial continuity has been reestablished. Our results indicate that the replicative and phenotypic properties of cultured IT-15 cells clearly differ from those of the UM (and of course from those of the control media).…”
Section: Cell-populated Collagen Lattice Contractionmentioning
confidence: 99%
“…Key Words: smooth muscle cells Ⅲ apoptosis Ⅲ reactive oxygen species Ⅲ hydrogen peroxide Ⅲ neointima R ecent reports by several groups indicate that smooth muscle cells (SMCs) within the arterial wall comprise a variety of distinct phenotypes that possess unique biochemical and functional properties. [1][2][3][4][5][6][7][8] In general, clonally derived SMC lines can be classified as "fusiform" or "epithelioid," corresponding to the appearance and growth pattern of the cells in culture. 2,9 Fusiform SMCs, which are elongated and exhibit the classic "hills-and-valleys" pattern of growth, are predominant in the arterial media of adult animals.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In general, clonally derived SMC lines can be classified as "fusiform" or "epithelioid," corresponding to the appearance and growth pattern of the cells in culture. 2,9 Fusiform SMCs, which are elongated and exhibit the classic "hills-and-valleys" pattern of growth, are predominant in the arterial media of adult animals.…”
mentioning
confidence: 99%